CONCENTRATION OF LACTIC ACID, AMMONIA AND PH OF CASSAVA WASTE SILAGE PROVIDING DIFFERENT LEVEL OF MOLLASES - Ridwan, M.; Saefulhadjar, D.; Hernaman, I. (Majalah Ilmiah Peternakan; Vol 23 No 1 (2020): Vol. 23 No.1 (2020), 2020)
The research aims to preserve cassava plantation waste using molasses additives. The study was conducted experimentally using a completely randomized design consisting of 4 treatments and 5 replications. The resulting data were analyzed for variance at the level of ? = 0.5% and continued with the Duncan test. The treatment was in the form of the use of molasses at 0% (P0), 2% (P1), 4% (P2), and 6 % (P3). The results showed that the lactic acid content increased significantly (P<0.05) with P4 producing the highest value, which is 6.90 mM. The pH value at the P0 treatment was higher (P <0.05), but ammonia concentration decreases compared to the treatment using molasses. The relationship between lactic acid and pH showed a negative correlation with the regression equation was y = -0.3634X + 6.0886 and the correlation value (r) of 0.65, while the relationship between pH and ammonia resulted in a regression equation y = 1.9835X - 0.2064 with a correlation value of r that is 0.64. The results concluded that molasses can increase levels of lactic acid, but reduce the pH and ammonia and use as much as 2% to provide an optimal ensilage process.